Association between Air Pollution Relating to Agricultural Residue Burning and Morbidity of Acute Cardiopulmonary Diseases in Upper Northern Thailand - Wongsanuphat, Suphanat; Praekunatham, Hirunwut; Jitpeera, Charuttaporn; Thammawijaya, Panithee (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2024)
In Northern Thailand, increasing seasonal agricultural residue burning has led to public concern about health risks. This study aimed to examine the associations between air pollutants related to agricultural residue burning and morbidity from acute cardiopulmonary diseases in upper Northern Thailand in 2018. An ecological study was conducted. Emergency room visits and hospitalizations for chronic obstructive pulmonary disease (COPD), stroke, myocardial infarction (MI), and asthma were extracted from the National Electronic Health Record database. We interpolated air pollution data to estimate weekly pollutant concentrations, including PM10, PM2.5, carbon monoxide, nitrogen dioxide, sulfur dioxide and ozone from 1 Jan to 31 Dec 2018. Associations between air pollution and health outcomes were analyzed using a mixed effect model incorporating different lag structures. Overall pollutant concentrations exceeded WHO air quality standard levels throughout March and April, which is the end of forest burning prohibition campaign. Morbidity from COPD, stroke, MI and asthma slightly increased over March–April. For every increase in PM2.5 level of 10 μg/m3, the relative risk of COPD, stroke, MI and asthma 1 week later was 1.10 (95% CI 1.09–1.12), 1.06 (1.05–1.08), 1.06 (1.04–1.08) and 1.06 (1.01–1.12), respectively. The effects of agricultural residue burning should be highlighted and policies should be developed to deter this practice.